A pena e a espada: projetos de Brasil em Edgard Leuenroth - Gonçalves, Cláudia Tolentino (2014)
The aim of this study is to analyze two guide-projects written by the anarchist militant Edgard Leuenroth: O que é maximismo ou bolchevismo um programa comunista (1919), which he wrote with Hélio Negro, and Qual a solução para o problema do Brasil?, manuscript he began organizing in the 1960s, but left unfinished because his of death in 1968. We call \"guide-projects\" because they\'re about political projections (based on the possible construction of the anarchy in Brazil) and guidetexts, because they elaborate lots of measures and strategies that guide the revolutionary process and the post-revolutionary act. Considering the scope of both projects, we selected for analysis some of this anarchiist militant main thought categories, such as direct action, property, solidarity, syndicate, federalism, reform/revolution and order/disorder.